Immunohistochemical analysis of p53 expression in anal squamous neoplasia. Issue 6 (June 1993) - Ogunbiyi, O A; Scholefield, J H; Smith, J H; Polacarz, S V; Rogers, K; Sharp, F
Abstract : AIMS–To determine the pattern of expression of the p53 tumour suppressor gene product in anal squamous neoplasia, and to determine if this could be used as a marker of disease progression. The association between p53 expression and human papillomavirus (HPV) 16 DNA status of the anal lesions was also investigated. METHODS–The presence and localisation of the p53 protein in formalin fixed, paraffin wax embedded specimens of anal squamous epithelium (normal and neoplastic) was examined using immunohistochemical staining with a panel of two monoclonal antibodies (DO-1, DO-7) and one polyclonal antibody (CM-1). Thirty nine normal anal epithelia, 14 anal intraepithelial neoplasia (AIN) grade 1, seven AIN 2, and 20 AIN 3 specimens were obtained from patients without demonstrable invasive disease; twelve AIN 3 specimens adjacent to invasive disease and 34 anal squamous cancers were also examined. Genomic DNA from all 126 specimens was extracted and analysed for HPV 16 DNA using the polymerase chain reaction (PCR). RESULTS–Nuclear p53 was strongly expressed in 67% (23/34) of invasive anal squamous tumours, 75% (9/12) of AIN 3 specimens adjacent to invasive disease, and in 60% (12/20) of AIN 3 specimens obtained from patients without demonstrable invasive disease. Two of the patients in the latter group with positively staining specimens subsequently developed invasive tumours which had staining characteristics similar to those of the AIN 3 specimens. p53 protein was expressed in very low concentrations in low grade AIN and not at all in normal anal squamous epithelium. In those specimens which stained positively for p53, HPV 16 DNA sequences were detected in 69.5% (16/23) of invasive disease, 77.7% (7/9) of AIN 3 adjacent to invasive disease, 75% (9/12) of AIN 3 obtained from patients without demonstrable invasive disease, 33.3% (2/6) of AIN 2, and in 40% (2/5) of AIN 1. There was no significant correlation between p53 immunostaining and HPV 16 DNA status (p < 0.05). CONCLUSIONS–Aberrant expression of the p53 gene product is probably involved in the pathogenesis of anal squamous neoplasia. Long term follow up studies of all patients with AIN are required to determine if this could be used as a marker of likely disease progression from high grade AIN to invasive disease. There does not seem to be an association between the presence or absence of HPV 16 DNA sequences and mutant p53 proteins in anal squamous neoplasia.